2009
DOI: 10.1523/jneurosci.5120-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Low-Threshold Primary Afferent Drive onto GABAergic Interneurons in the Superficial Dorsal Horn of the Mouse

Abstract: Inhibition in the spinal cord dorsal horn is crucial for maintaining separation of touch and pain modalities. Disruption of this inhibition results in allodynia, allowing low-threshold drive onto pain and temperature-sensitive projection neurons. This low-threshold (LT) excitatory pathway is normally under strong inhibition. We hypothesized that superficial dorsal horn inhibitory neurons, which would be ideally located to suppress LT drive onto projection neurons in a feedforward manner, are driven by LT input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 60 publications
(116 reference statements)
10
109
0
2
Order By: Relevance
“…Dorsal horn functional circuitry is incompletely mapped out, but lamina II GABAergic interneurons are ideally located to gate the flow of nociceptive information from the periphery to supraspinal areas. Previous studies have shown that these interneurons receive both highthreshold and low-threshold primary afferent input (67), and innervate NK1R-expressing projection neurons (21,68), therefore being positioned to provide inhibitory control over dorsal horn nociceptive circuitry. We hypothesize that IL-1β released from microglia or astrocytes rapidly potentiates glycinergic synapses on GABAergic lamina II interneurons that normally inhibit the passage of nociceptive signals to the brain; after inflammation, the nociception-transmitting neurons will in turn be rapidly disinhibited via this mechanism, enhancing the perceived pain and contributing to hyperalgesia and allodynia (44).…”
Section: Glycine Receptor Trafficking and Channel Properties Modulatementioning
confidence: 99%
“…Dorsal horn functional circuitry is incompletely mapped out, but lamina II GABAergic interneurons are ideally located to gate the flow of nociceptive information from the periphery to supraspinal areas. Previous studies have shown that these interneurons receive both highthreshold and low-threshold primary afferent input (67), and innervate NK1R-expressing projection neurons (21,68), therefore being positioned to provide inhibitory control over dorsal horn nociceptive circuitry. We hypothesize that IL-1β released from microglia or astrocytes rapidly potentiates glycinergic synapses on GABAergic lamina II interneurons that normally inhibit the passage of nociceptive signals to the brain; after inflammation, the nociception-transmitting neurons will in turn be rapidly disinhibited via this mechanism, enhancing the perceived pain and contributing to hyperalgesia and allodynia (44).…”
Section: Glycine Receptor Trafficking and Channel Properties Modulatementioning
confidence: 99%
“…According to the gate control theory (Melzack and Wall, 1965), nociceptive spinothalamic tract neurons are dynamically regulated by inhibition from various sources, including innocuous afferent inputs, which drive interneurons in the superficial dorsal horn (Daniele and MacDermott, 2009). In animals with injured nerves, spinothalamic tract neurons show increased responsiveness to innocuous mechanical stimuli (Palecek et al, 1992).…”
Section: Spinal Mechanism Underlying the Initial Phase Of Neuropathicmentioning
confidence: 99%
“…(Daniele and MacDermott, 2009). Third, inhibitory neurons of lamina II receive input from both LT and high-threshold (HT) primary afferents (Daniele and MacDermott, 2009), but we considered only the LT drive from Aβ-fibers.…”
Section: Identified Synaptic Connections Technical Approach Physiologmentioning
confidence: 99%
“…(Daniele and MacDermott, 2009). Third, inhibitory neurons of lamina II receive input from both LT and high-threshold (HT) primary afferents (Daniele and MacDermott, 2009), but we considered only the LT drive from Aβ-fibers. Fourth, the excitatory central cell reported by Lu and Perl (2005) was assumed to be tonic instead of transient (it actually fires rapidly but briefly to sustained depolarizations).…”
Section: Identified Synaptic Connections Technical Approach Physiologmentioning
confidence: 99%
See 1 more Smart Citation